Combined systemic and intraventricular chemotherapy in primary CNS lymphoma: a pilot study. Issue 1 (1st July 2001) - Schlegel, U; Pels, H; Glasmacher, A; Kleinschmidt, R; Schmidt-Wolf, I; Helmstaedter, C; Flieβbach, K; Deckert, M; Van Roost, D; Fimmers, R; Bode, U; Klockgether, T
Abstract : The objective was to evaluate response rate, response duration, and toxicity after systemic and intraventricular chemotherapy in primary CNS lymphoma (PCNSL).  From September 1995 to September 1998, 20 consecutive patients with PCNSL (median age 64, range 27 to 71 years) were enrolled in a pilot study evaluating chemotherapy without radiotherapy. A high dose methotrexate (MTX) (cycles 1, 2, 4, 5) and cytarabine (ara-C) (cycles 3, 6) based systemic therapy (including dexamethasone, vinca alkaloids, ifosfamide, and cyclophosphamide) was combined with intraventricular MTX, prednisolone, and ara-C.  Complete response was achieved in 11 and partial remission in two patients; in one response could not be determined. Four patients showed progressive disease and two (70, 71 years) died from treatment related complications. Observation time was 2 to 59 months (median 31.5 months). Kaplan-Meier estimate for median time to treatment failure (TTF) was 20.5 months, and for median survival 54 months. Systemic toxicity was mainly hematological. Ommaya reservoir infection occurred in four patients and acute transient MTX induced encephalopathy in two (subacute in another). Cognitive dysfunction possibly due to treatment was seen in only one patient after relapse and after a total of 12 cycles (six at relapse).  In conclusion, primary chemotherapy based on high dose MTX and ara-C is highly efficient in PCNSL. Toxicity is manageable in patients younger than 70 years.